2011
DOI: 10.1111/j.1471-0528.2011.03031.x
|View full text |Cite
|
Sign up to set email alerts
|

False‐positive pregnancy tests following enterocystoplasty

Abstract: People with major congenital urological or neurological malformations invariably require bladder reconstruction with enterocystoplasty in early childhood. The improvement of the surgical management of these children has reflected significantly on their life expectancy. As a result, more young people with enterocystoplasty are being transitioned to adolescent clinics where they receive the usual counselling about sexual health and pregnancy risks. However, the possibility of false-positive urinary pregnancy tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…When urine is stored in an intestinal segment, urine pregnancy tests often produce a false positive result (>50%), making serum HCG assay essential to confirm or rule out pregnancy. 49,50 Bacteriuria is classified as symptomatic or asymptomatic, the former often do not need systemic treatment, although increased fluid intake and more frequent emptying are warranted. Symptoms such as fever, malaise or increased incontinence merit early evaluation and culture to allow tailored antibiotic management.…”
Section: Discussionmentioning
confidence: 99%
“…When urine is stored in an intestinal segment, urine pregnancy tests often produce a false positive result (>50%), making serum HCG assay essential to confirm or rule out pregnancy. 49,50 Bacteriuria is classified as symptomatic or asymptomatic, the former often do not need systemic treatment, although increased fluid intake and more frequent emptying are warranted. Symptoms such as fever, malaise or increased incontinence merit early evaluation and culture to allow tailored antibiotic management.…”
Section: Discussionmentioning
confidence: 99%
“…The false-negative result of a home pregnancy test kit causes an increased in pregnancy and sexually transmitted infections (Rahman and Berenson 2013). The home pregnancy test kit's false-positive results lead to significant patient anxiety and pointless interventions (Nakhal et al 2012). It is also observed that the point of care glucose meter's accuracy and clinical performance is hindered at some level of performance (Watkinson et al 2012), through the unsuitable glucose meter may overestimate and underestimate the glucose level, which may hamper the insulin dose of the patient (Perera et al 2011).…”
Section: Limitations Of µPads For Poctmentioning
confidence: 99%